Enabling innovation innovative capability - German and international views - Jeschke, Sabina; Isenhardt, Ingrid; Hees, Frank; Trantow, Sven (Springer eBooks., 2011)
The capability to innovate in an on-going manner is emerging as a decisive key factor in today's world of business and work. The ability to stay competitive is becoming identical with the ability to innovate. This book originated from the research and development project "International Monitoring" and outlines the topic of innovative capability from a practice-oriented angle. Contributions of German and international experts offer an enlightening glimpse behind the scenes of innovations. The central issue is not the description of features of successful innovation processes or how innovations can be efficiently controlled and managed, but under which conditions they can emerge in the first place. In what way can individuals, organizations, networks and societies be enabled to continuously induce innovations?